STUDY OF LAND CAPABILITY SUITABILITY ON LAND COVER AND SPATIAL PLANNING IN WEST BANDUNG REGENCY - Aulia, Redha
Spatial planning of an area must consider its environmental carrying capacity, and one way to do so is by identifying its land capability. West Bandung Regency (KBB) is a part of the Bandung Metropolitan Area that has been impacted by rapid urban development and urbanization. KBB has experienced environmental degradation due to the lack of alignment between land allocation and its land capability. KBB is also prone to hydro-meteorological disasters. The objective of this study is to assess the suitability of land cover and the spatial planning based on the land capability in KBB. Thematic spatial data, including flood threats, drainage, soil types, geology, and land cover in 2018, as well as the spatial planning for KBB from 2012 to 2032, were obtained from relevant institutions in KBB. The land capability analysis in this study considers constraint factors such as slope, erosion sensitivity, drainage, flood threats, and soil texture. Spatial analysis was conducted using a Geographic Information System (GIS). The results of the study indicate that KBB is predominantly classified as class VIII, which signifies a severe constraint factor, covering 51.67% of the total area, indicating that the land allocation should be for conservation areas. Furthermore, the study found that the majority of land cover in KBB in 2018 (43.30%) does not align with its land capability. This mismatch is evident in land cover for plantations, agriculture, open fields, and settlements. Regarding the spatial planning for KBB, it was found that 46.31% of the planning is fairly aligned with its land capability, although there are still areas (38.34%) that are not fully aligned, such as residential and other activity areas, production forest areas, agricultural areas, and plantation areas. The inconsistency between land cover and spatial planning in accordance with land capability highlights the need for monitoring actual land allocation and reviewing the spatial planning. This study provides valuable input for spatial policy makers and authorities to avoid potential negative externalities resulting from the mismatch between the land capability and land use in the future.